Pathological studies on the ameliorative effect of curcumalonga on experimental pasteurellosis in rabbits - Manjula V James (Centre for Excellence in Pathology, College of Veterinary and Animal Sciences, 2008)
An experiment was conducted to evaluate the symptoms and lesions of experimental pasteurellosis and to study the beneficial effects of Curcuma longa (turmeric) in managing pasteurellosis. Thirty two New Zealand white rabbits were divided into four groups each having eight replicates. Group I served as control. Group II were given feed mixed with turmeric at the rate of 2 g/kg body weight for the whole period of experiment and on the thirty first day of the experiment, animals were intranasally exposed to P. multocida. Group III rabbits were intranasally exposed to P. multocida on the thirty first day of the experiment and turmeric was fed at the rate of 2 g/ kg body weight after exposure until the end of the experiment. Group IV rabbits were fed on control diet alone for thirty days and then intranasally exposed to P. multocida on the thirty first day of the experiment. Body weight and haematological parameters were recorded on day zero, 14th and 28th day of the experiment and biochemical parameters on 28th day were estimated. The rabbits were challenged with 0.1 ml of 18 h broth culture of P. multocida serotype A: 1 containing approximately 3 ×108 organisms/ml by intranasal route. Blood was collected for haematological and biochemical evaluations after eighteen hours of post inoculation from all the groups. Supplementation of turmeric significantly (P<0.05) increased the body weight on 28th day of the experiment. Turmeric supplementation significantly (P<0.05) increased the haemoglobin concentration on day 28. The total leukocyte count and differential leukocyte count did not reveal significant difference between the dietary groups. The serum total protein, albumin and albumin : globulin ratio were significantly (P<0.05) higher in turmeric fed group on the 28th day. The serum creatinine values were within the normal range and no significant difference was noticed. The levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST) and alkaline phosphatase (ALP) were comparatively lower in turmeric fed group but no significant difference were noticed on the 28th day. Results of the present study after challenge with P. multocida indicated that the haemoglobin concentration did not reveal significant difference except for numerical decrease in values noted in challenged groups compared to the control. The total leukocyte count and differential leukocyte count significantly (P<0.05) increased in challenged groups compared to the control. Also the levels of serum total protein, albumin: globulin ratio and creatinine were significantly (P<0.05) higher in challenged groups. The levels of ALT, AST and ALP were also significantly (P<0.05) higher in the challenged groups. Pathological studies on the trachea, lungs, heart, liver and kidney revealed acute lesions suggestive of septicaemia. The intensity of damage in Group II rabbits were found to be much less in these organs which were evident in the haemato-biochemical values and gross and histopathological lesions. Overall evaluation of the results of the study indicated that supplementation of turmeric was advantageous. Also the study brought to the light that apart from the beneficial effects on body weight, haematology and biochemical profile, turmeric revealed partial protective role on pasteurellosis. The results of the study prove promising and need further investigation using different levels of turmeric in diets.